2018
DOI: 10.1039/c7ra13523h
|View full text |Cite
|
Sign up to set email alerts
|

In situ green oxidation synthesis of Ti3+ and N self-doped SrTiOxNy nanoparticles with enhanced photocatalytic activity under visible light

Abstract: A simple in situ green oxidation synthesis route was developed to prepare Ti3+ and N self-doped SrTiOxNy nanoparticles using TiN and H2O2 as precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Secondly, the NTO/Pt/Ni catalyst has a higher surface area and pore volume than the other samples, implying a higher number of active sites for adsorption of ethanol-water molecules. Third, according to XPS, calculated Ti 3+ /Ti 4+ ratios of the NTO/Ni/Pt catalyst present a higher quantity of oxygen vacancies which also correspond to reactive sites for the reaction [50]. Fourth, NTO/Pt/Ni apparently presents more Pt 2+ species than Pt 4+ ones, the Pt being the reduced species that is more efficient for photocatalytic hydrogen production [51][52][53].…”
Section: Catalysts Synthesismentioning
confidence: 96%
“…Secondly, the NTO/Pt/Ni catalyst has a higher surface area and pore volume than the other samples, implying a higher number of active sites for adsorption of ethanol-water molecules. Third, according to XPS, calculated Ti 3+ /Ti 4+ ratios of the NTO/Ni/Pt catalyst present a higher quantity of oxygen vacancies which also correspond to reactive sites for the reaction [50]. Fourth, NTO/Pt/Ni apparently presents more Pt 2+ species than Pt 4+ ones, the Pt being the reduced species that is more efficient for photocatalytic hydrogen production [51][52][53].…”
Section: Catalysts Synthesismentioning
confidence: 96%
“…For example, the Ti 3+ self-doped SrTiO 3 samples prepared in this paper are more stable than Ti–N doped SrTiO 3 samples compared to currently available studies. 38 The results showed that the Ti 3+ self-doped strontium titanate prepared by the molten salt electrochemical method had good photocatalytic stability. The SEM of STO-1.8 after 8 cycles is shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…These two peaks further deconvoluted into four peaks, which are Ti 3+ 2p 3/2 (458.7 eV), Ti 4+ 2p 3/2 (459.6 eV), Ti 3+ 2p 1/2 (464 eV), and Ti 4+ 2p 1/2 (465.1 eV). 39,40 In S0, the intensity and area of Ti +3 peaks are significantly higher than those of Ti +4 peaks, confirming the oxygen-deficient nature of the pure TiO 2 nanotube array. However, in SrTiO 3 −TiO 2 heterostructured nanotube array samples, oxygen deficiency is diminished, and Ti 4+ peaks are dominated over Ti +3 (Figure 4a).…”
Section: ■ Experimental Sectionmentioning
confidence: 82%